2024
DOI: 10.1039/d3ra08507d
|View full text |Cite
|
Sign up to set email alerts
|

N-doped CNTs wrapped sulfur-loaded hierarchical porous carbon cathode for Li–sulfur battery studies

Arunakumari Nulu,
Venugopal Nulu,
Keun Yong Sohn

Abstract: Hierarchical porous carbon structures are prepared by KOH activation process from coffee waste and are encapsulated with sulfur followed by N-CNTs wrapping. As a cathode for Li–S batteries, the electrode showed excellent electrochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…To underscore the significance and merits of this study, a comparison was made between the capacity decay rate of Li–S batteries utilizing the carbon nanotube-based cathode and the capacity decay rate reported in a recently published study on lithium–sulfur batteries at a current density of 0.5 C, as depicted in Figure c. The data indicated that, when compared with other flexible carbon nanofibers, the PCNF sandwich structure electrode exhibited a lower capacity decay rate, offering a promising outlook for Li–S batteries with exceptional cycle performance, the detailed data are illustrated in Table S1 (Supporting Information: Comparison of average decay rate per cycle of the PCNF/T with that of recent publications in Li–S batteries).…”
Section: Resultsmentioning
confidence: 94%
“…To underscore the significance and merits of this study, a comparison was made between the capacity decay rate of Li–S batteries utilizing the carbon nanotube-based cathode and the capacity decay rate reported in a recently published study on lithium–sulfur batteries at a current density of 0.5 C, as depicted in Figure c. The data indicated that, when compared with other flexible carbon nanofibers, the PCNF sandwich structure electrode exhibited a lower capacity decay rate, offering a promising outlook for Li–S batteries with exceptional cycle performance, the detailed data are illustrated in Table S1 (Supporting Information: Comparison of average decay rate per cycle of the PCNF/T with that of recent publications in Li–S batteries).…”
Section: Resultsmentioning
confidence: 94%